Natural attenuation method for contaminant remediation reagent delivery assessment for in situ chemical oxidation using aqueous ozone. (May 2020) - Khan, Naima A.; Carroll, Kenneth C.
Abstract: A Monitored Natural Attenuation (MNA) assessment approach typically used for contaminant remediation feasibility assessment was developed here for remediation-reagent delivery assessment. Subsurface delivery of oxidants, such as aqueous ozone (O3 ) for in situ chemical oxidation (ISCO) of groundwater contaminants, is naturally attenuated by oxidant demand and reactivity. We compared mixed reactor kinetic experiments, sand column tracer transport experiments, and reactive transport modeling and assessment methods to quantify natural attenuation kinetics, aqueous O3 solute transport, oxidant demand kinetics, and ISCO reagent delivery limitations. Sorption of aqueous O3 to quartz sand was observed during transport of O3 through water-saturated porous media. Pseudo 1st order decomposition rate constants of O3 bulk attenuation with transport were comparable to mixed reactor experiments without transport, and reactive transport modeling of miscible-displacement column experiments was used to quantify each attenuation process. Aqueous ionic strength was correlated with O3 decomposition rate constants, which was the dominant reagent delivery attenuation process. These results suggest that aqueous O3 decomposition and oxidant delivery attenuation can be predictable upon characterization of the sediment oxidant demand and dispersion, and increasing groundwater velocity during aqueous O3 injection can maximize transport distance for reagent delivery. Highlights: MNA assessment methods for contaminant treatment reagent delivery assessment. Aqueous ozone solute transport through porous media with both decay and sorption. Mixed reactors, transport experiments, and modeling had comparable rate constants. Comparable methods for quantification of reagent delivery attenuation kinetics. Abstract : Natural attenuation method was developed for contaminant remediation reagent delivery assessment for ISCO using aqueous ozone.